2017
DOI: 10.1109/jstqe.2017.2719403
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward III–V Bismide Alloys for Near- and Midinfrared Laser Diodes

Abstract: The manufacturing industry is regarded as one of the most demanding verticals with respect to URLLC requirements. A Device-to-Device (D2D) communication system is a key enabler that has been introduced to support URLLC. To enhance spectrum utilisation, D2D links can share access of radio spectrum resources occupied by cellular users. Spectrum reuse may result in performance degradation due to mutual co-channel interference of co-existing cellular and D2D users. Resource sharing in a D2D-based cellular network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 83 publications
0
44
0
2
Order By: Relevance
“…It is worth noting that the value of T 0 is similar to the previously reported GaAsBi lasers (T 0 =90∼125 K), indicating T 0 may be independent of Bi composition. 33 For the previously mentioned QW lasers of optimized 12% Al in barrier layer T 0 is equal to 100 K above RT. 11 This indicates that the low T 0 for GaAsBi LDs was mainly due to the non-radiative recombination caused by Bi-related defects.…”
Section: Fig 2 Depicts Both Voltage-current (V-imentioning
confidence: 99%
“…It is worth noting that the value of T 0 is similar to the previously reported GaAsBi lasers (T 0 =90∼125 K), indicating T 0 may be independent of Bi composition. 33 For the previously mentioned QW lasers of optimized 12% Al in barrier layer T 0 is equal to 100 K above RT. 11 This indicates that the low T 0 for GaAsBi LDs was mainly due to the non-radiative recombination caused by Bi-related defects.…”
Section: Fig 2 Depicts Both Voltage-current (V-imentioning
confidence: 99%
“…During the past decade, most of the focus has been on developing near-infrared band gap GaAsBi based structures on GaAs substrates. This has resulted in the demonstration of electrically pumped quantum well (QW) lasers with bismuth compositions of up to 6% and maximum room temperature lasing wavelengths of 1142 nm [10,11,12]. The threshold current densities of these devices are relatively high compared to bismuth-free material which has been shown to be due to defect-related recombination [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in the demonstration of electrically pumped quantum well (QW) lasers with bismuth compositions of up to 6% and maximum room temperature lasing wavelengths of 1142 nm [10,11,12]. The threshold current densities of these devices are relatively high compared to bismuth-free material which has been shown to be due to defect-related recombination [11,13]. The main limiting factors affecting the devices are non-radiative recombination via defects and inhomogeneity effects caused by low temperature growth and difficulties of bismuth incorporation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GaSbBi alloys have not been explored much, in contrast to GaAsBi alloys, which have been extensively studied in recent years by several groups. [14][15][16][17][18][19][20][21][22][23][24] In the case of GaAsBi, it is observed that Bi tends to segregate toward the surface and to form droplets due to its large size in comparison with arsenic. Therefore, the growth of III-V-Bi materials is usually achieved using very-low growth temperatures and a near stoichiometric V/III ratio.…”
mentioning
confidence: 99%